Nasal microRNA signatures for disease severity in infants with respiratory syncytial virus bronchiolitis: a multicentre prospective study - Carlos A Camargo; Kohei Hasegawa; Zhaozhong Zhu; Tadao Ooka; Andrea Hahn; Marcos Pérez-Losada; Jonathan M Mansbach; Michihito Kyo; Ryohei Shibata; Brennan Harmon (BMJ Open Respiratory Research, 2024)
Background Respiratory syncytial virus (RSV) bronchiolitis contributes to a large morbidity and mortality burden globally. While emerging evidence suggests that airway microRNA (miRNA) is involved in the pathobiology of RSV infection, its role in the disease severity remains unclear.Methods In this multicentre prospective study of infants (aged<1 year) hospitalised for RSV bronchiolitis, we sequenced the upper airway miRNA and messenger RNA (mRNA) at hospitalisation. First, we identified differentially expressed miRNAs (DEmiRNAs) associated with higher bronchiolitis severity—defined by respiratory support (eg, positive pressure ventilation, high-flow oxygen therapy) use. We also examined the biological significance of miRNAs through pathway analysis. Second, we identified differentially expressed mRNAs (DEmRNAs) associated with bronchiolitis severity. Last, we constructed miRNA–mRNA coexpression networks and determined hub mRNAs by weighted gene coexpression network analysis (WGCNA).Results In 493 infants hospitalised with RSV bronchiolitis, 19 DEmiRNAs were associated with bronchiolitis severity (eg, miR-27a-3p, miR-26b-5p; false discovery rate<0.10). The pathway analysis using miRNA data identified 1291 bronchiolitis severity-related pathways—for example, regulation of cell adhesion mediated by integrin. Second, 1298 DEmRNAs were associated with bronchiolitis severity. Last, of these, 190 DEmRNAs were identified as targets of DEmiRNAs and negatively correlated with DEmiRNAs. By applying WGCNA to DEmRNAs, four disease modules were significantly associated with bronchiolitis severity—for example, microtubule anchoring, cell-substrate junction. The hub genes for each of these modules were also identified—for example, PCM1 for the microtubule anchoring module, LIMS1 for the cell-substrate junction module.Conclusions In infants hospitalised for RSV bronchiolitis, airway miRNA–mRNA coexpression network contributes to the pathobiology of bronchiolitis severity.